2021
DOI: 10.1186/s12978-021-01203-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of common risk factors between polycystic ovary syndrome and Alzheimer’s disease: a narrative review

Abstract: Background The most common endocrine and metabolic disorders in premenopausal women is polycystic ovary syndrome (PCOS), characterized by hyperandrogenism, chronic anovulation, and/or ultrasound evidence of small ovarian cysts. Obesity and insulin resistance are also the main factors influencing the clinical manifestations of this syndrome. Alzheimer’s disease (AD) is the most typical progressive neurodegenerative disorder of the brain, and recent studies suggest a relationship between endocrin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 116 publications
(140 reference statements)
0
7
0
Order By: Relevance
“…Studies of PCOS and risk of cognitive decline, dementia, and Alzheimer’s disease are lacking, but the postulation has been made that increased risk may be associated with chronic inflammation, obesity, insulin resistance, and androgenic-mediated effects on the central nervous system that affect cognitive function. 138 …”
Section: Discussionmentioning
confidence: 99%
“…Studies of PCOS and risk of cognitive decline, dementia, and Alzheimer’s disease are lacking, but the postulation has been made that increased risk may be associated with chronic inflammation, obesity, insulin resistance, and androgenic-mediated effects on the central nervous system that affect cognitive function. 138 …”
Section: Discussionmentioning
confidence: 99%
“…The various ApoE isoforms differ in their ability to bind lipids and amyloid-β, a critical protein in Alzheimer’s disease [ 36 ]. This finding of increased levels of ApoE may be pertinent in protecting against the potential increased risk of Alzheimer’s disease in PCOS, where it has been shown that these subjects may share some common risk factors [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…VD3 has implicated in bone metabolism, but recently it has been identified as a potential contributor to the extraosseous pathophysiological conditions in many tissues and organs, including brain [17,24,25], kidney [26], immune system [27], skin [28], and others. Our previous results showed accelerated wound repair with VD3 but without complete repair [8].…”
Section: Discussionmentioning
confidence: 99%